Perifosine enhances mTORC1-targeted cancer therapy by activation of GSK3β in NSCLC cells - Ma, Zhuo (Landes Bioscience, 2012)
mTORC1 inhibitors, including rapamycin and its analogs, have been actively studied both pre-clinically and clinically. However, the single treatment of mTORC1 inhibitors has been modest in most cancer types. We have previously demonstrated that the activation of PI3K/Akt and MEK/ERK signaling pathways attenuates the anticancer efficacy of mTORC1 inhibitors. In this study, we report that mTORC1 inhibition also phosphorylates and inactivates GSK3β, which is a tumor suppressor in lung cancer. Moreover, we show that perifosine, as an Akt inhibitor, decreases rapamycin-induced phosphorylation of GSK3β and elevated p-GSK3β levels in rapamycin-resistant cell lines. Combination of perifosine with mTORC1 inhibitors showed enhanced anticancer efficacy both in cell cultures and in a xenograft mouse model. In addition, perifosine inhibits the growth of both rapamycin sensitive and resistant A549 cells. However, inhibition of GSK3β by a selective inhibitor- LiCl, or downregulation of GSK3β expression by siRNA, reverses the growth inhibitory effects of perifosine on rapamycin resistant cells, suggesting the important role of GSK3β activation in enhancing mTORC1 inhibitors efficacy by perifosine. Thus, our results provide a potential therapeutic strategy to enhance mTORC1-targeted cancer therapy by using perifosine or targeting GSK3β.